Recent Developments in the Analysis of the Black Mat Layer and Cosmic Impact at 12.8 ka. Issue 1 (6th December 2013) - Mahaney, William C.; Keiser, Leslie; Krinsley, David H.; West, Allen; Dirszowsky, Randy; Allen, Chris C.R.; Costa, Pedro
Abstract Recent analyses of sediment samples from "black mat" sites in South America and Europe support previous interpretations of an ET impact event that reversed the Late Glacial demise of LGM ice during the Bølling Allerød warming, resulting in a resurgence of ice termed the Younger Dryas (YD) cooling episode. The breakup or impact of a cosmic vehicle at the YD boundary coincides with the onset of a 1‐kyr long interval of glacial resurgence, one of the most studied events of the Late Pleistocene. New analytical databases reveal a corpus of data indicating that the cosmic impact was a real event, most possibly a cosmic airburst from Earth's encounter with the Taurid Complex comet or unknown asteroid, an event that led to cosmic fragments exploding interhemispherically over widely dispersed areas, including the northern Andes of Venezuela and the Alps on the Italian/French frontier. While the databases in the two areas differ somewhat, the overall interpretation is that microtextural evidence in weathering rinds and in sands of associated paleosols and glaciofluvial deposits carry undeniable attributes of melted glassy carbon and Fe spherules, planar deformation features, shock‐melted and contorted quartz, occasional transition and platinum metals, and brecciated and impacted minerals of diverse lithologies. In concert with other black mat localities in the Western USA, the Netherlands, coastal France, Syria, Central Asia, Peru, Argentina and Mexico, it appears that a widespread cosmic impact by an asteroid or comet is responsible for deposition of the black mat at the onset of the YD glacial event. Whether or not the impact caused a 1‐kyr interval of glacial climate depends upon whether or not the Earth had multiple centuries‐long episodic encounters with the Taurid Complex or asteroid remnants; impact‐related changes in microclimates sustained climatic forcing sufficient to maintain positive mass balances in the reformed ice; and/or inertia in the Atlantic thermohaline circulation system persisted for 1 kyr.